Pengaruh Insentif dan Pengembangan Karir terhadap Loyalitas Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada CV. Mala Sari - Syati Manaharawan Siregar; Nur Ainun; Surya Alamsyah Putra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study aims to determine how much influence incentives and career development and job satisfaction (intervening variables) have on loyalty in CV. Malasari. This study uses a quantitative descriptive method with a normative approach (legal research) to obtain secondary data and an empirical approach (sociological juridical), to obtain primary data through field research (field research). The results showed that the effect of incentives, career development and job satisfaction on loyalty in CV. Malasari, based on the indicators are as follows: First, the effect of incentives on loyalty has a positive and significant effect which if it increases, loyalty will also increase. Second, the influence of career development on loyalty has a positive and significant effect where if career development increases, loyalty will also increase. Third, the effect of job satisfaction on loyalty has a positive and significant effect which means that job satisfaction increases, loyalty will also increase. Fourth, the influence of career development on job satisfaction has a positive effect, which means that if career development increases, job satisfaction will also increase. Fifth, the effect of incentives on job satisfaction has a positive effect, which means that if incentives increase, job satisfaction will also increase. Sixth, the effect of career development on loyalty that is intervened by job satisfaction is smaller than the direct effect of career development on loyalty. Seventh, the effect of incentives on loyalty that is intervened by job satisfaction is smaller than the direct effect of incentives on loyalty. Which is better than the two variables, namely career development and intensification not to be interfered with by job satisfaction. For that, it is hoped that CV. Malasari in terms of improving loyalty so that employees pay more attention to incentives, career development and job satisfaction on CV. Malasari. In order to create good Loyalty in CV. Malasari